KEEFEKTIFAN MODEL TGT DAN JIGSAW DENGAN PENDEKATAN SAINTIFIK PEMBELAJARANEKONOMI SMA NEGERI DI SLEMAN - Hariyanto, Agus; Zuchdi, Darmiyati (Harmoni Sosial: Jurnal Pendidikan IPS, 2016)
Tujuan penelitian ini untuk menguji: (1) keefektifan model Teams Games Tournament (TGT)  dan model  Jigsaw dengan pendekatan saintifik, (2)  membandingkan keefektifan model TGT  dan Jigsaw dengan pendekatan saintifik dalam pembelajaran ekonomi SMA Negeri di Kabupaten Sleman. Penelitian ini merupakan penelitian eksperimen semu dengan desain pretest postest non equivalent group design.  Populasi penelitian adalah siswa kelas X SMA Negeri di Kabupaten Sleman. Hasil penelitian sebagai berikut: 1) Model TGT dan Jigsaw dengan pendekatan saintifik efektif  meningkatkan hasil belajar ranah kognitif, afektif, dan psikomotorik. 2) Ada perbedaan keefektifan signifikan antara model TGT dan Jigsaw. Model Jigsaw mempunyai jumlah indeks gain score ranah kognitif, afektif, dan psikomotoriklebih tinggi dibandingkan TGT. Model TGT mempunyai gain score lebih tinggi dibandingkan dengan Jigsaw untuk hasil belajar ranah kognitif. Model Jigsaw mempunyai gain score lebih tinggi dibandingkan dengan TGT untuk hasil belajar ranah afektif. Model TGT dan Jigsaw menunjukkan gain score yang sama  untuk hasil belajar ranah psikomotorik.THE EFECTIVENESS OF THE TGT AND JIGSAW MODELS USING THESCIENTIFIK APPROACHIN ECONOMICS LEARNINGAT STATE SHSs IN SLEMAN AbstractThis study aims to test: (1) the effectiveness of the Teams Games Tournament (TGT)  and Jigsaw modelsusing  the scientific approach. (2) tocompare the effectiveness of the TGT and Jigsaw models using the scientific approach in economics learning at state SHSs in Sleman Regency. This was a quasi-experimental study pretest postest non equivalent group design employing the pretest-posttest design. The research population comprised Grade X students of state SHSs in Sleman Regency. The results of the study are as follows. 1) The TGT and the Jigsaw modelswhich are implemented using the scientific approach effectivelyimproves the learning outcome in the cognitive, affective, and psychomotoric domains. 2) There isa significant difference in terms of effectiveness between the two models. Jigsaw model is generates a higher gain score than TGT that was indicated by results of the sum of index gain score cognitive,  affective, and psychomotoric aspects learning outcomes. The TGT learning model generates a higher gain score than the Jigsaw for the cognitive domain. The Jigsaw model, however, produces a higher gain score than the TGT  for the affective domain. Compared to the Jigsaw model, the TGT learning model shows an equal gain score for the psychomotoric domain.